Risk factor analysis and economic effects to Rotavirus A (RVA) in backyard swine farms the case of the districts of Bunawan, Calinan, Toril and Tugbok in Davao City - Gilles, Pierre Giuseppe P. (2017)
Swine is considered a major source of meat in the Philippines and it is mainly produced through backyard farming. Rotavirus A (RVA) poses threat to swine production since it causes diarrhea which could affect nutrition absorption and swine live weight. Thereby affecting returns for swine farmers. This study used three methods in understanding the relationship between backyard swine farming and RVA incidence in Davao City backyard farms: risk analysis; production function estimation; and the cost and returns. Backyard farms from four districts in Davao City were surveyed and the district selection was based on the records of relevant government agencies. Among the management practices and environmental characteristics considered for the risk factor analysis, the use of drain, improvised or technically made, significantly reduced the likelihood of RVA incidence. For the production function estimation, feeding materials, labor, and year of experience were significant drivers that positively affected swine live weight. On the other hand, backyard swine farms that were tested positive for RVA had negative impact on swine live weight compared to those without RVA detection. Thus, minimizing RVA incidence could help increase returns to scale of backyard swine production. When farms were pooled, return in investment(ROI) and return on sales (ROS) of backyard swine farming were 64.07% and 33.73% respectively. However, farms without RVA detection had higher ROI and ROS compared to those with RVA detection. In particular, farms without RVA detection tend to have higher returns and higher costs, especially in labor. The findings of this study point out the need to invest on proper caretaking in backyard swine farms especially to maintain good sanitation to reduce RVA incidence. This also calls for the need to understand how other pathogens affecting backyard swine production would be associated with the actual productivity and profitability of these farms.